2018
DOI: 10.1002/chem.201802298
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious Preparation of Open‐Cage Fullerenes by Rhodium(I)‐Catalyzed [2+2+2] Cycloaddition of Diynes and C60: An Experimental and Theoretical Study

Abstract: A novel methodology to transform C into a variety of open-cage fullerene derivatives by employing rhodium(I) catalysis has been developed. This transformation encompasses a partially intermolecular [2+2+2] cycloaddition reaction between diynes 1 and C to deliver a cyclohexadiene-fused fullerene, which concomitantly undergoes a formal [4+4]/retro-[2+2+2] rearrangement to deliver open-cage fullerenes 2. Most notably, this process occurs without the need of photoexcitation. The complete mechanism of this transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 100 publications
2
25
0
Order By: Relevance
“…The open-cage derivatives used in this study, 2a – c , were prepared by the photochemical oxidation of bis(fulleroids) 1a – c , which can be obtained from [60]fullerene in one step using our Rh(I)-catalyzed cycloaddition protocol (Scheme 1) [41]. Importantly, unlike precursors 1a - c , open-cage derivatives 2a – c do not suffer further degradation upon exposure to light and air.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The open-cage derivatives used in this study, 2a – c , were prepared by the photochemical oxidation of bis(fulleroids) 1a – c , which can be obtained from [60]fullerene in one step using our Rh(I)-catalyzed cycloaddition protocol (Scheme 1) [41]. Importantly, unlike precursors 1a - c , open-cage derivatives 2a – c do not suffer further degradation upon exposure to light and air.…”
Section: Resultsmentioning
confidence: 99%
“…However, their use as ETLs in PSCs remains unexplored. Some of us recently reported a straightforward methodology for the synthesis of open-cage fullerene derivatives (Scheme 1) [41,42]. The promising electrochemical properties and remarkable stability of these compounds, together with the fact that fullerene derivatives are so far the materials of choice as the ETL for p-i-n PSCs, prompted us to study the use of these compounds for PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…We were able to show that the reaction, when catalyzed by [Rh(cod) 2 ]BF 4 and Tol-BINAP, not only worked with great efficiency but also allowed for the s121 direct preparation of open-cage fullerenes 323 (Scheme 121). 322 We completed our experimental work by performing a computational study with the M06-L-D3/cc-pVTZ-PP// B3LYP-D3/cc-pVDZ-PP method of the reaction mechanism of the intermolecular [2 + 2 + 2] cycloaddition of the 1,6-diyne of Scheme 121 and C 60 catalyzed by [RhBINAP] + . To reduce the computational cost, the tosyl group of the 1,6-diyne was substituted by a mesyl group and, in the catalyst ligand, the tolyl groups were replaced by methyl groups and the binaphthyl was Rothwell et al 325,326 reported the selective synthesis of 1,3cyclohexadiene scaffolds by reaction of two alkynes and one olefin under catalysis by titanacyclopentadiene (162c) or s124 titanacyclopentane (329) aryloxide complexes (Scheme 124).…”
mentioning
confidence: 99%
“…As a result, it undergoes a variety of chemical organic reactions, the most important being the nucleophilic additions [4][5][6]. Moreover, C 60 reacts through many metal-catalysed processes like the Pauson-Khand reactions [7][8][9], the Suzuki-Miyaura reactions [10][11][12][13] or the [2 + 2 + 2] cycloadditions [14][15][16], among others. However, one of the most employed reactions for the functionalization of fullerenes and their derivatives is the Diels-Alder (DA) cycloaddition [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%